The Emergence of Sabahan Telemovies and Cultural Representation - Sibangan, S.T.; Lee, T.M.; Siang, T.S; Abdullah, Q.D.L.; Jali, A. (Universiti Malaysia Sarawak (UNIMAS), 2019)
The advent of digital technology in filmmaking has a tremendous effect on film production in the digital era. One of the advantages of digital filmmaking is lower production cost and a minimal workforce, and these have benefited many low-budget independent film production. In particular, Sabahan telemovies production has been benefited from technological advancement. The telemovie, Proton Saga Kelabu that produced in early 2000 marks the emergence of Sabahan telemovie production. In 2004, Sabahan telemovie director, Abu Bakar Ellah directed Percintaan Tanpa Izin (PTI) that depicts a profound sense of Sabahan cultural identity. This paper aims to examine the emergence of Sabah telemovie production and to discuss the Sabah cultural identity that represented in the telemovie PTI. Through a close analysis of the telemovie, the discussion focused on the representation of Sabah cultural identity in the aspects of shooting location, native language and traditional costume that emblematized in the telemovie.